Identification and virulence factors prediction of Didymella segeticola causing leaf spot disease in Asarum heterotropoides in China - Kun Liu; Wensong Sun; Xiaoli Li; Baoyu Shen; Tianjing Zhang; Chunlei Yu (Scientific Reports)
Abstract Chinese wild ginger (Asarum heterotropoides Fr. Schmidt var. mandshuricum (Maxim.) Kitag) is a perennial medicinal herb in China. In May 2022, 25 leaf-spot Asarum plants were collected. Employing tissue-separation and single-spore-isolation techniques, 37 fungal strains were obtained, of which seven were Didymella-like strains. Through multi-locus phylogeny and morphology analyses, these seven strains were identified as Didymella segeticola, with stain Xy0531-4 designated as the representative. In multi-locus phylogeny analysis, the concatenated fragments in the series were 1422 bp, including 395 bp of ITS, 532 bp of LSU, 358 bp of rpb2, and 137 bp of tub2. Pathogenicity tests confirmed that D. segeticola is the causal agent of Asarum leaf spot in China. Furthermore, through bioinformatic analyses, 87 putative virulence-associated proteins were encoded in the reference genome. Based on phenotypic annotations in PHI-base, these factors were categorized into three functional classes: lethal (54 proteins, associated with pathogen gene TOXA), increased virulence (hypervirulence) (19 proteins, associated with pathogen genes ChVel1 and ChLae1), and effector (plant avirulence determinant) (14 proteins, associated with pathogen genes SRE1, Cgfl, StACE1 and RsRplA). In addition, PPI network and k-means clustering analyses revealed significant phenotypic specificity in the interaction patterns of the leaf spot-associated virulence factors. These findings provide novel insights into the molecular mechanisms underlying the pathogenicity of D. segeticola, laying a foundation for future research on Asarum-leaf-spot disease management strategies.